Analysis and countermeasures of indwelling gastric tube insertion into left pulmonary bronchus in a patient with nasopharyngeal carcinoma (1例鼻咽癌患者留置胃管误入左肺支气管的护理体会) - LIU Qiong (刘琼); WU Aidi (吴爱弟); HU Suqin (胡素勤); YU Mengjia (于梦佳) (中西医结合护理)
This paper summarized the nursing countermeasures of indwelling gastric tube insertion into left pulmonary bronchus in a patient with nasopharyngeal carcinoma. Disease, anatomical position, material of catheters and other issuers are influencing factors of insertion indwelling gastric tube into pulmonary bronchus. Nurses should take risk factor into consideration before catheter placement, and adopt standard methods to determine the position of catheter tip. (本文总结1例浅昏迷鼻咽癌患者留置胃管误入左肺支气管的护理经验。疾病、解剖位置、置管材料等均是导致置管误入气管的高危因素, 护士在执行胃管操作时应积极评估上述危险因素, 采取科学、规范的方法准确判断置管位置, 避免不良事件发生。)